Higher efficacy of a single dosage albendazole and different soil-transmitted helminths re-infection profiles amongst indigenous Negritos from inland jungle versus those in resettlement at town peripheries - Muslim, Azdayanti (Malaysian Society of Parasitology and Tropical Medicine, 2022)
Demarginalization through initiation of resettlement program since 1978 is an inevitable progress faced by the indigenous Orang Asli (OA) population in Peninsular Malaysia. As Malaysian hunter -gatherers, the Negrito has been exposed to various environmental-cultural variations. These changes may influence the pattern of soil-transmitted helminth (STH) infections, the common malady amongst OA. This study evaluated the deworming effects of single-dosage albendazole (400 mg) and STH-reinfection rate between Negritos who are still living in the inland jungle versus those living in resettlements at town peripheries (RPS). Stool samples from the consented participants were first examined using the direct faecal smear, formalin-ether sedimentation and Kato Katz techniques. Subsequently, stool collections were carried out in three time points following treatment (i.e., 21 days, 3 months and 6 months). In brief, a total number of 54 Negritos (inland: 24; RPS: 30) with a complete set of stool collection was included in this longitudinal study. This study revealed 72.2% cure rate against T. trichiura in the inland but only 15.0% in the RPS. Although the efficacy of albendazole against T. trichiura was ultimately low in the RPS, 62.6% egg reduction rate (ERR) (arithmetic mean) was noted (p = 0.001). For A. lumbricoides and hookworm, high cure rates were found in both communities (85.7-100.0%). Reinfection for T. trichiura was seen in less than 1 month with higher rate in the RPS (90.0%) as opposed to the inland (44.4%) at 21 days following treatment. This study found that the inland OA had better tolerability to single-dosage albendazole and experienced slower STH reinfection rates versus the RPS. Hence, the selection of albendazole dosage should be targeted and the use of single-dosage albendazole (biannually) would be more suitable for the inland OA. Conversely, we propose the use of 3-days albendazole regimens in the resettled RPS population.